2017
DOI: 10.1111/jeb.13049
|View full text |Cite
|
Sign up to set email alerts
|

Signalling of information that is neither cryptic nor private

Abstract: It is commonly assumed that in order for animal signals to be advantageous, the information being signalled could not have been obtained otherwise, and is therefore 'cryptic' or 'private'. Here, we suggest a scenario in which individuals can gain an advantage by signalling 'public' information that is neither cryptic nor private. In that scenario, signalling increases the efficiency with which that 'public' information is transmitted. We formalize our idea with a game in which offspring can signal their condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Cues are typically classified as non‐signalling traits because, by definition, they have not evolved for the purpose of conveying information to receivers (Maynard Smith and Harper ; Wild et al. ). However, cues of quality do experience signalling selection: they vary with signaller quality, receivers respond to that variation, and receiver responses affect signaller fitness.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Cues are typically classified as non‐signalling traits because, by definition, they have not evolved for the purpose of conveying information to receivers (Maynard Smith and Harper ; Wild et al. ). However, cues of quality do experience signalling selection: they vary with signaller quality, receivers respond to that variation, and receiver responses affect signaller fitness.…”
Section: Discussionmentioning
confidence: 72%
“…More generally, the model will apply to analogous contexts, including offspring signalling their need to parents (Godfray ; Wild et al. ) and plants signalling their quality to pollinators or herbivores (Archetti and Brown ; Knauer and Schiestl ). In our approach, males have a signalling strategy that matches their quality to a particular signal size, and females have a strategy that infers signaler quality from signal size.…”
Section: Resultsmentioning
confidence: 99%
“…In nature, R. imitator may depend on parents because parents are selected to deposit them in nutrient‐poor nurseries (Brown et al, 2010; Brown, Morales, & Summers, 2008a; Brown, Twomey, et al, 2008), but offspring traits do not contribute to this dependence. While co‐evolution of parents and offspring is often driven by conflict (Mock & Parker, 1997; Trivers, 1974), cooperative traits can also evolve if their costs are low (Wild et al, 2017); plasticity that enables offspring to efficiently convert parental investment into fitness may be one such example of cooperation within families.…”
Section: Discussionmentioning
confidence: 99%
“…While these pheromone signals are publically broadcast into the environment, correct interpretation of them could be specific to an ecological community or kin group. In support of this idea, game theory studies have shown that public signals can evolve [ 40 ].…”
Section: Elegans Pheromone Signallingmentioning
confidence: 99%